Effects of high temperature on residual punching strength of slab-column connections after cooling and enhanced post-punching load resistance. (15th November 2019) - Zhang, Chunyu; Ma, Wenchen; Liu, Xiang; Tian, Ying; Orton, Sarah L.
Highlights: A detailing approach to enhance post-punching strength of slab-column connections. Residual strength of slab-column connections after cooling from high temperatures. High temperatures up to 800 °C were applied to slab compression face. Applied high temperature did not cause serious shear strength reduction. Finite element simulations for post-heating strength of slab-column connections. Abstract: Large-scale experiments were conducted on six isolated slab-column connection specimens. Each specimen contained a 300 mm square center column and a 150 mm thick slab. The objectives of the experiments were to study the effects of fire-induced high temperatures on the residual punching shear strength of reinforced concrete flat-plate structures after cooling and to examine the effectiveness of a detailing approach for enhancing the post-punching load-carrying capacity. Ceramic fiber heating panels were used to apply high temperatures to slab shear-critical regions at the compressive face. The test results indicate that the high temperatures up to 800 °C did not seriously impact connection punching shear strength. Moreover, the use of crossties can effectively engage slab tensile reinforcement in resisting post-punching loads with a loading capacity close to or even greater than the punching failure load. Complementary to experiments, finite element simulations were conducted. The numerical simulations predicted the punching failure load of slab-column connections at room temperature with a good accuracy; however, the simulations underestimated the post-heating punching strength of the cooled slab-column connections by up to 11%.